Mining Spillovers in Chile - Perez Ruiz, Esther (IMF Working Papers; Working Paper, 2017)
Chile's small open economy with significant mismatch between the production and consumption baskets may be represented by three stylized sectors, a commodity sector, a non-commodity tradable sector, and a non-tradable sector. This paper estimates the effect of copper price shocks on mining, manufacturing, and construction-each embodying a sector type. The empirical findings are for positive spillovers from mining to the other two sectors. However, the estimated size of the spillovers seems modest, which raises the question of the potential for mining to be better integrated with the rest of the economy.